Terrestrial and Martian Space Weather: A Complex Systems Approach - Stepanova, M (Elsevier Ltd, 2024)
A comparative overview of Terrestrial and Martian space weather is presented, with emphasis on applying the tools of complexity and nonlinear dynamics to study the spatiotemporal dynamics and structures of sun–Earth and sun–Mars space environment. The following topics are reviewed: (1) complex systems approach to solar atmosphere and solar wind; (2) complex systems approach to planetary bow shock and magnetosphere–ionosphere; (3) Martian space weather, bow shock, and magnetosphere–ionosphere; (4) imaging planetary magnetosphere–ionosphere. © 2024 The Author(s)